Population Growth and Environmental Damage Issues (A Review of Environmental Damage on Land Conversion Perspective in North Jakarta) - Hamzah, A Hadian Pratama; Nurhasanah, Nurhasanah; Soesanta, Prabawa Eka (Graduate Program Magister Manajemen Pendidikan, 2023)
Population and environmental issues are two things that are not being separated from one another. Humans along with other living creatures are a component of life that always interact with the environment. The ecosystem itself is the order of the ecological elements. This study will describe how the impact of population density on social, economic and ecological aspects of changes in an area undergoing conversion in Jakarta Bay. Literature and comparative studies of results from various sources in journal articles are primary data used as main data in the analysis of population and environmental damage studies. The results of this study describe how the total area of ​​mangrove forest and changes in coastline experienced by shifting caused by the increase in residential areas due to population density in the Jakarta Bay North Jakarta. The study related to changes in the area of ​​mangrove forests and coastlines, especially connected due to residential development from land consumption due to population density in Jakarta Bay.